(3GdSOQI GdaQjOI aj TQM GdbUjOI (B( (3GdTGWHjI GdeYQhaI HMQR GdCeGfi (B)s - (3efJLH GdOjf MSjf Hf CHi GdYR Hf GdQTjO GdgePGfi GdTaYhis; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3jHJOF ef Chd GdbUjOI s
(3BNQgG (B:s
(3Edi HGH (B" (3GdGXgGQ hGdGOZGe (B" s
(3bUjOI LQR GdCeGfi GdeSeGI HGdbUjOI GdTGWHjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B9 s
Keywords: (3GdbQGAGJ hGdJLhjOs